PEMENTASAN DRAMA DENGAN PENDEKATAN PROJECT BASED LEARNING SEBAGAI UPAYA PEMBEKALAN ARTISTIK PERTUNJUKAN BAGI MAHASISWA CALON GURU - Akhmad fatoni; Achmad Dipoyono; Deni Mustopa; Rani Jayanti (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2020)
This research was conducted because the trigger for theater performances in Mojokerto has always decreased from year to year, especially school theaters. The student theater festival, which is held annually, has not been held for two years. The trigger for the school to allow and finance the show did not exist. The purpose of this research is to find a solution to the decreasing productivity of performances in Mojokerto. The method used is a single case study method. This case study stage uses a "detailed descriptive analysis". The finding of this research is that the theater must be held with a fun concept. Teachers (read: prospective teachers) when they are equipped with stage layout can be a trigger for the return of school theater through the ability of teachers to organize performances. At the same time creating a trigger to change the concept of the show with a makeshift management pattern, into a professional management pattern. Keyword: Contextual Teaching and Learning, artistic performance stage layout, School Theater.